Generalized lichen nitidus in an 11-year-old boy. - Ahuja, S.R.; Pandey, T.; Phiske, M.; Someshwar, S. (European Journal of Pediatric Dermatology, 2022)
Lichen nitidus (LN) is rare, chronic inflammatory, papular eruption, characterized by asymptomatic, pinhead-sized papules on neck, trunk, limbs, abdomen and penile shaft. It is often localized, but can be generalized. Here is reported a case of generalized lichen nitidus in an 11-year-old boy successfully treated with systemic corticosteroids and tacrolimus ointment.